Memories of near-death experiences: are they self-defining?. Issue 1 (1st March 2019) - Cassol, H; D'Argembeau, A; Charland-Verville, V; Laureys, S; Martial, C
Abstract: Some people report memories of near-death experiences (NDEs) after facing situations of impending death and these memories appear to have significant consequences on their lives (here referred to as "real NDE experiencers"; real NDErs). We assessed to what extent NDE memories are considered self-defining: memories that help people to define clearly how they see themselves. We screened 71 participants using the Greyson NDE scale (48 real NDErs and 23 NDErs-like who had lived a similar experience in absence of a threat to their life). Participants described their two main self-defining memories (SDMs). For each SDM, they completed the Centrality of Event Scale (CES) to assess how central the event is to their identity. The two subgroups did not differ regarding the proportion of NDErs who recalled their NDE (30 real NDErs out of 48 and 11 NDErs-like out of 23). Real NDErs and NDErs-like who recalled their NDE ( n = 41) reported richer experiences as assessed by the Greyson NDE scale. Furthermore, these participants rated their NDE memory as more central to their identity as compared to other SDMs, and the richness of the NDE memory was positively associated to its centrality (CES scores). Overall, these findings suggest that the self-defining aspect of the experience might be related to its phenomenological content rather than its circumstances of occurrence. The self-defining status of NDE memories confirms that they constitute an important part of NDErs' personal identity and highlights the importance for clinicians to facilitate their integration within the self.